Nanoelectronics, nanophotonics, and quantum technologies - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, Haifeng (World Scientific, 2025)
Keywords: Field (mathematics); Quantum; Quantum computer; Quantum dot; Quantum entanglement; Quantum technology; dept.phy

High performance materials and devices for high-speed electronic systems - Jain, F; Broadbridge, C; Tang, H; Gherasimova, M (World Scientific Publishing Co. Pte. Ltd., 2018)
In this review volume, the editors have included the state-of-the-art research and development in nano composites, and optical electronics written by experts in the field. In addition, it also covers applications for emerging technologies in High-Speed Electronics. In summary, topics covered in this volume includes various aspects of high performance materials and devices for implementing High-Speed Electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: Emerging technologies; High performance material; High-speed electronics; Materials; Nanocomposites; Optical electronics; State of the art; dept.phy

High performance logic and circuits for high-speed electronic systems - Jain, F; Broadbridge, C; Gherasimova, M; Tang, H (World Scientific Publishing Co., 2019)
In this volume, we have put together papers spanning a broad range from the area of modeling of strain and misfit dislocation densities, microwave absorption characteristics of nanocomposites, to X-ray diffraction studies. Specific topics in this volume include: Modeling of strain relaxation and defect dynamics in buffer layers for semiconductor devices fabricated on lattice-mismatched substrates, which enables technology for advanced computer chips, multi-junction solar cells, detectors, and microwave transistors. Physical Unclonable Functions (PUFs) are probabilistic circuit primitives that extract randomness from the physical characteristics of devices. One of the papers outlines PUF design based on resistor and capacitor variations for low pass filters (LoPUF). Spatial wavefunction switching (SWS) FETs, which can process 2-bits per FET using CMOS-SWS logic, thus enabling multivalued logic (MVL) and compact DRAMs. Perimeter gated single-photon avalanche diode (PGSPAD). The applied voltage at the gate terminal modulates the electric field, making it uniform throughout the junction. This gating technique is an efficient method to prevent premature edge breakdown, one of the major problems in operating avalanche photodiodes implemented in CMOS process. In summary, papers selected in this volume cover various aspects of high performance logic and circuits for high-speed electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (High Performance Logic and Circuits for High-Speed Electronic Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.C.; Broadbridge, C.; Tang, H.; Gherasimova, M. (High Performance Materials and Devices for High-Speed Electronic Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: Materials; dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H.; Gherasimova, M. (International Journal of High Speed Electronics and Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (Nanostructures For Electronics, Photonics, Biosensors, And Emerging Systems Applications, 2022)
0 citations (Crossref) [2023-10-31] ISBN: 9789811270796
Keywords: dept.phy

Nanotechnology in Electronics, Photonics, Biosensors and Energy Systems - Jain, F.; Braodbridge, C.; Gherasimova, M.; Hong, X. Tang (2023)
Pages: undefined Publication Title: Selected topics in electornics and systems
Keywords: dept.phy

Nanoelectronics, Nanophotonics, And Quantum Technologies: Devices And Applications - Jain, Faquir C.; Broadbridge, C.; Gherasimova, M.; Tang, Hong (World Scientific, 2025)
This timely compendium provides state-of-the-art articles covering research areas in Nanoelectronics, Nanophotonics and Quantum Technologies.Composed of contributions by renowned researchers from both the academia and industry, this useful reference text broadly illustrates relevant aspects of high-performance materials and emerging quantum and nanoscale devices for implementing high-speed electronic systems.
Google-Books-ID: h_K0EQAAQBAJ
Keywords: Computers / Quantum Computing; Technology & Engineering / Nanotechnology & MEMS; dept.phy

MOCVD growth and characterization of AlGaInN nanowires and nanostructures - Han, J.; Kim, K.; Su, J.; Gherasimova, M.; Nurmikko, A.V.; Chichibu, S.F.; Broadbridge, C. (Mater Res Soc Symp Proc, 2006)
Growth of GaN and AlGaInN nanowires using metalorganic chemical vapor deposition (MOCVD) is investigated. It is determined that surface kinetics play an important role in non-equilibrium synthesis process such as MOCVD, in contrast to near-equilibrium synthesis by hotwall furnace reactor. Examination of crystallographic properties of GaN nanowires reveals preferential growth directions which are perpendicular to the c-axis. Such a tendency is analyzed by both thermodynamic and kinetic arguments and attributed to the minimization of (side wall) surface energy. Spontaneous formation of Al(Ga)N/GaN coaxial nanowires with distinct emission at 370 nm is observed. It is identified that the interplay between surface kinetics and thermodynamics facilitates the catalytic growth of GaN core while a limited surface diffusion of Al adatoms leads to nonselective, vapor-solid growth of Al(Ga)N sheath. The knowledge of crystallographic alignment is applied to the formation of arrayed GaN nanowires in both vertical and horizontal fashions, resulting in potentially new paradigms for creating nanoscale devices. © 2006 Materials Research Society.
Journal Abbreviation: Mater Res Soc Symp Proc
Keywords: Crystal growth; Crystallography; Diffusion; Growth directions; Interfacial energy; Metallorganic chemical vapor deposition; Nanostructured materials; Nanostructures; Nanotechnology; Nanowires; Semiconductor quantum wires; dept.phy; non equilibrium synthesis

Bridging the length scales between lithographic patterning and self assembly mechanisms in fabrication of semiconductor nanostructure arrays - Hull, Robert; Floro, J A; Gherasimova, M; Graham, J; Gray, J L; Portavoce, A; Ross, Frances M; Thorp, J (Journal of Physics: Conference Series, 2010)
We employ focused ion beam patterning of single crystal Si(100) surfaces to template the assembly of Ge(Si) nanostructure arrays. The evolution and final structures of the templated arrays are determined by combinations of transmission electron, low energy electron microscope, focused ion beam and scanning probe microscopies. It is shown how the positions of individual nanostructures may be controlled to the order of 10 nm. However, to achieve controlled spacings between elements that are in the 10 nm range requires careful matching of the characteristic lengths scales of self assembly mechanisms to the length scales of the external lithographic "forcing functions". © 2010 IOP Publishing Ltd.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-366-191-463-372
Keywords: Assembly mechanism; Characteristic length; Electrons; Focused ion beams; Germanium; Ion beams; Lithographic patterning; Low energy electron microscopes; Nanostructure arrays; Nanostructures; Self assembly; Semiconductor nanostructures; Silicon wafers; Single crystal surfaces; Single crystals; Single-crystal Si; Transmission electron; dept.phy

Nanotechnology for Electronics, Photonics, Biosensors, and Emerging Technologies - Jain, F.; Broadbridge, C. C.; Gherasimova, M.; Tang, H.; Connecticut Microelectronics and Optoelectronics Consortium New Haven, Conn) (World Scientific, 2021)
Keywords: Congresses; Congresses; Biosensors; Congresses; Nanoelectronics; Congresses; Nanophotonics; Congresses; Optoelectronics; Nanotechnology; dept.phy; faculty_collection

Growth of AlGaN nanowires by metalorganic chemical vapor deposition - Su, J.; Gherasimova, M.; Cui, G.; Tsukamoto, Hironori; Han, J.; Onuma, T.; Kurimoto, M.; Chichibu, Shigefusa F.; Broadbridge, Christine; He, Y.; Nurmikko, Arto V. (Applied Physics Letters, 2005)
Growth of ternary AlGaN nanowires using metalorganic chemical vapor deposition is investigated. Structural, chemical, and optical characterization at nanoscopic scale is carried out by high resolution transmission electron microscopy, x-ray energy dispersive spectroscopy, and spatially resolved cathodoluminescence. Spontaneous formation of Al (Ga) NGaN coaxial nanowires with distinct emission at 370 nm is observed. It is identified that the interplay between surface kinetics and thermodynamics facilitates the catalytic growth of GaN core while a limited surface diffusion of Al adatoms leads to nonselective, vapor-solid growth of Al(Ga)N sheath. The observation points to a fundamental difference in nanosynthesis using near-equilibrium and nonequilibrium techniques. © 2005 American Institute of Physics.
37 citations (Crossref) [2023-10-31] Citation Key Alias: pop00071 tex.type: [object Object]
Keywords: Aluminum compounds; Cathodoluminescence; Coaxial nanowires; Energy dispersive spectroscopy; Metallorganic chemical vapor deposition; Nanoscopic scale; Nanostructured materials; Optical properties; Reaction kinetics; Surface kinetics; Synthesis (chemical); Transmission electron microscopy; X-ray energy dispersive spectroscopy; dept.phy

Vapor-liquid-solid growth of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition - Su, J; Gherasimova, M; Cui, G; Han, J; Lim, Sangyun; Ciuparu, Dragos; Pfefferle, Lisa D; He, Y; Nurmikko, A V; Broadbridge, Christine; Lehman, Ann Hein; Onuma, T; et al. (MRS Proceedings, 2004)
We report flexible synthesis of III-Nitride nanowires and heterostructures by metal-organic chemical vapor deposition (MOCVD) via a catalytic vapor-liquid-solid (VLS) growth mechanism. Indium is used as an in-situ catalyst to facilitate and sustain the stability of liquid phase droplet for VLS growth based on thermodynamic consideration. The employment of mesoporous molecular sieves (MCM-41) helps to prevent the coalescence of catalyst droplets and to promote nucleation statistics. Cathodoluminescence (CL) of GaN nanowires shows near band-edge emission at 370nm, and strong E 2 phonon peak is observed at room temperature in Raman scattering spectra. Both binary GaN and AlN nanowires have been synthesized by MOCVD. Three-dimensional AlN/GaN trunk-branch nanostructures are reported to illustrate the versatility of incorporating the VLS mechanism into MOCVD process. © 2005 Materials Research Society.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-591-869-918-808 tex.type: [object Object]
Keywords: Catalysis; Heterojunctions; Metallorganic chemical vapor deposition; Molecular beam epitaxy; Nanoelectronics; Nanostructured materials; Nanowires; Nucleation; Optical characterization; Synthesis (chemical); Thermodynamics; Vapor-liquid-solid (VLS) growth; dept.phy

Catalytic growth of group III-nitride nanowires and nanostructures by metalorganic chemical vapor deposition - Su, J; Cui, G; Gherasimova, M; Tsukamoto, Hironori; Han, J; Ciuparu, Dragos; Lim, Sangyun; Pfefferle, Lisa D; He, Y; Nurmikko, A V; Broadbridge, Christine; Lehman, Ann Hein (Applied Physics Letters, 2005)
We report flexible synthesis of group III-nitride nanowires and nanostructures by metalorganic chemical vapor deposition (MOCVD) via a catalytic vapor-liquid-solid (VLS) growth mechanism. Supersaturation and surface stoichiometry strongly influence the stability of liquid droplets and growth selectivity. To facilitate and sustain the VLS growth, indium catalyst is introduced based on thermodynamic consideration. The employment of mesoporous molecular sieves (MCM-41) helps to prevent the coalescence of catalyst droplets and to promote nucleation statistics. Both GaN and AlN nanowires have been synthesized using MOCVD. Three-dimensional AlNGaN trunk-branch nanostructures are reported to illustrate the versatility of incorporating the VLS mechanism into MOCVD process. © 2005 American Institute of Physics.
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/046-539-752-343-072 tex.type: [object Object]
Keywords: Catalysis; Catalysts; Growth kinetics; Indium; Metallorganic chemical vapor deposition; Molecular sieves; Nanostructured materials; Nanowires; Nitrides; Nucleation; Scanning electron microscopy; Stoichiometry; Supersaturation; Synthesis (chemical); Thermodynamics; Transmission electron microscopy; Trimethyl-gallium (TMGa); Trimethylaluminum (TMAl); Vapor-solid-liquid (VLS) growth mechanism; dept.phy